2017
DOI: 10.2147/jpr.s134133
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Pain Traumatization Scale: development, validation, and preliminary findings

Abstract: BackgroundThis article reports three studies describing the development and validation of the 12-item Sensitivity to Pain Traumatization Scale (SPTS-12). SPT refers to the anxiety-related cognitive, emotional, and behavioral reactions to pain that resemble the features of a traumatic stress reaction.MethodsIn Study 1, a preliminary set of 79 items was administered to 116 participants. The data were analyzed by using combined nonparametric and parametric item response theory resulting in a 12-item scale with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 59 publications
2
64
0
Order By: Relevance
“…Postoperative pain contributes to increased morbidity, impaired physical function and quality of life, slowed recovery, prolonged opioid use during and after hospitalization, and increased cost of care. Moreover, early postoperative pain can trigger persistent pain that may last for months after surgery 22. The rate of chronic pain after hysterectomy is reported to range from 5%–32% 23.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain contributes to increased morbidity, impaired physical function and quality of life, slowed recovery, prolonged opioid use during and after hospitalization, and increased cost of care. Moreover, early postoperative pain can trigger persistent pain that may last for months after surgery 22. The rate of chronic pain after hysterectomy is reported to range from 5%–32% 23.…”
Section: Discussionmentioning
confidence: 99%
“…These models emphasize the mechanistic and high association between pain severity, vulnerability to anxiety-related cognitive, emotional and behavioural reactions to pain, and attentional biases towards threat in the development of both persistent pain and PTSS. 25 Previous studies have found that shared vulnerability symptoms play a large role—more so than symptoms like low mood 32 —in the persistence of pain after surgery 34 or injury. 52 The associations that we identified between specific PTSS and pain outcomes support the presence of shared mechanisms, especially the perception of more severe pain, and greater physiological and cognitive reactivity to both the trauma and to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes were perceptions of IDB use in terms of acceptability, traumatism (pain, iatrogenia, sensibility) and efficacy, rated with Likert scales scored from 1 (very good) to 5 (very bad). This 3 criteria have priority to ensure the patient's engagement [ 14 16 ]. The latter requires the practice of the good hygiene methods taught on the disorganization of the interdental biofilm and use of the material recommended by the practitioner.…”
Section: Methodsmentioning
confidence: 99%